Determinants of contemporary entrepreneurship - Majkut, Robert (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
The article discusses theoretically and empirically relative deprivation and the existential mechanism as factors of entrepreneurship. Motivation to engage in entrepreneurial activity based on relative deprivation is the result of a discrepancy between the level of aspirations and the degree of their actual realisation. In such a situation there is a desire to act in order to achieve a higher standard of living. The existential mechanism, on the other hand, indicates that engaging in self-employment is a consequence of not being able to obtain the money necessary for satisfying needs in any other way. Both of these mechanisms can explain the reasons for engaging in self-employment for any individual, but they are largely suited to the analysis of immigrant entrepreneurship.